SISTEM INFORMASI NILAI AKADEMIS SISWA PADA SDIT SAKINAH KABUPATEN KAMPAR BERBASIS SMS GATEWAY - Alfirman Alfirman; Fatayat Fatayat (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
The development of information technology has now reached the world of education. One of the information technology that is developing at this time is SMS Gateway. In the world of education, SMS Gateway is needed because it can present a variety of information related to studentdevelopment.In this information system discusses about how the process of sending students academic value via SMS, sent from the system automatically (if students send SMS request value using a certain format)by using computerization.Assessment System on SDIT Sakinah ie, students get three report cards in each semester, consisting of two monthly report cards and semester report card. The distribution of semester report cards is distributed directly to the parents of the students at the end of each semester, while the monthly report card is given directly to the students without the accompanying parent/guardian who is sometimes not on time. Therefore, some of the problems that arise such as, after the test is held, students will come and always ask the teacher who teaches about the value obtained. This makes the inefficient time spent by students and teachers who teach.By using SMS gateway is expected to help students and also the school to streamline the time, and help parents/guardians to monitor the learning activities of children in school. So as to enhance the student's academic value.